The impact of hydrogen peroxide as an oxidant for solvent-free liquid phase oxidation of benzyl alcohol using Au-Pd supported carbon and titanium catalysts - Tareq, Sarhan Sanaa; Saiman, Mohd Izham; Yap, Taufiq Yun Hin; Abdullah, Abdul Halim; Rashid, Umer (Diponegoro University, 2018)
The solvent free oxidation of benzyl alcohol was conducted employing Au and Pd supported catalysts, while utilizing hydrogen peroxide 35% (H2O2) as the oxidant, H2O2 is very cheap, mild, and an environment friendly reagent, which produced water as the only by-product. Various proportions of Au-Pd catalysts on carbon and titanium oxide activated as supports were synthesized through the use of sol immobilization catalyst synthesis technique. Characterization of the synthesized catalysts was performed using X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), Field Emission Scanning Electron Microscopy (FESEM), and Transmission Electron Microscopy (TEM). It was found that the synthesized Au-Pd/ activated carbon catalyst was beneficial for the solvent free oxidation of benzyl alcohol after its containing high surface area measuring 871 m2g-1. Analysis of the TEM data and particle dimension revealed smaller and narrower particle size of 1 wt%. Thus, the distribution of Au-Pd/C was attained. Carbon-supported bimetallic catalysts presented a higher conversion compared to catalysts that are supported titanium oxide (TiO2) for for the oxidation reaction of benzyl alcohol. It was determined that this technique was a suitable process for catalyst synthesis with high selectivity, same distribution of the particle size and activations.